PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 001 KAMPAR TIMUR - Asmidar Asmidar; Syahrilfuddin Syahrilfuddin; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problems were found in the learning process which is an obstacle for this is the low social studies learning outcomes which have not yet reached KKM (minimum completeness criteria) as determined by the school is 64. It can be seen from the data of daily tests of class III Elementary School 001 Kampar Timur learning IPS with an average value of 62.82, the lowest score is 64 and the highest grade 75. classroom action Research aims to improve learning outcomes IPS third grade students of SDN 001 East Kampar, with the implementation of Cooperative learning Model GI. The research was conducted at a school that beralokasi in East SDN 001 Kampar Timur. This research was conducted in the second semester of the 2015/2016 academic year. The subjects were students of class III Elementary School 001 v, with the number of students 28 people, consisting of 9 men and 19 women. Berdasarkn results, it can be concluded that the model of cooperative learning type group investigation can improve learning outcomes IPS third grade students of SDN 001 Kampar Timur, seen from the results of learning basic score of 62.82 into 69.64 with an increase of 6.8. An increase from the first cycle to the second cycle, ie from an average of 69.64 into 77.86. Classical completeness of 33% of the 28 students in the first cycle increased by 75% in the second cycle completeness of students by 93%.Key Words: Learning Outcomes IPA, Group Investigation.